Horizontal bone augmentation using two membranes at dehisced implant sites: A randomized clinical study - Rakhshinda Nahid; Monika Bansal; Samidha Pandey (Elsevier, 2022)
Background: Placement of dental implant in narrow alveolar ridge is challenging to be treated. GBR procedure is currently most widely used to augment the deficient alveolar ridges and to treat the fenestration and dehiscence around dental implant. Thus, the objectives of the present study were to evaluate as well as compare the clinical performance of collagen membrane and titanium mesh for horizontal bone augmentation at dehisced implant sites. Methods and material: Total 12 single edentulous implant sites with buccal bone deficiency in 8 subjects were equally divided and treated simultaneously with either of the two membranes and DBBM(Bio-Oss) bone graft. Primary outcome measurements in terms of defect height and defect width were made using calibrated plastic periodontal probe. Re-entry surgery was performed to remeasure augmented site and to remove Ti-mesh at 6th months. Independent paired t-test for the inter-group comparison and student paired t-test for intra-group comparison were performed. The differences were considered to be significant at p ≤ 0.05. Results: Mean defect fill with respect to height and width was 3.50 ± 0.54 mm (87%) and 2.33 ± 0.51 mm (82%) for collagen membrane and 3.83 ± 0.75 mm (92%) and 2.50 ± 0.54 mm (88%) for Ti-mesh group respectively. Conclusions: Within the limitation of the study, it was concluded that mean defect height and width after 6 months were statistically significant within the group without significant difference between them, Although defect resolution was better in Ti-mesh.